2023
DOI: 10.1038/s41536-023-00306-2
|View full text |Cite
|
Sign up to set email alerts
|

DNA methyltransferase 1 deficiency improves macrophage motility and wound healing by ameliorating cholesterol accumulation

Chuanrong Zhao,
Qianru Yang,
Runze Tang
et al.

Abstract: Healing of the cutaneous wound requires macrophage recruitment at the sites of injury, where chemotactic migration of macrophages toward the wound is regulated by local inflammation. Recent studies suggest a positive contribution of DNA methyltransferase 1 (Dnmt1) to macrophage pro-informatory responses; however, its role in regulating macrophage motility remains unknown. In this study, myeloid-specific depletion of Dnmt1 in mice promoted cutaneous wound healing and de-suppressed the lipopolysaccharides (LPS)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…The diffusion constant for TAM diffusion roughly matches the time scale of motility of mouse nacrophages in transwell migration (68) and TAXIScan (69) assays which produce a range of speeds from roughly 0.55 − 1.0 𝜇/𝑚𝑖𝑛 (68). Table 1: All parameters are held fixed through all simulations except for the two rates which are estimated through the training process: the exhaustion rates of activated CD8+ T cells by both melanoma cells (𝑏 𝐶 ) and TAMs (𝑏 𝑀 ).…”
Section: Activatedmentioning
confidence: 52%
“…The diffusion constant for TAM diffusion roughly matches the time scale of motility of mouse nacrophages in transwell migration (68) and TAXIScan (69) assays which produce a range of speeds from roughly 0.55 − 1.0 𝜇/𝑚𝑖𝑛 (68). Table 1: All parameters are held fixed through all simulations except for the two rates which are estimated through the training process: the exhaustion rates of activated CD8+ T cells by both melanoma cells (𝑏 𝐶 ) and TAMs (𝑏 𝑀 ).…”
Section: Activatedmentioning
confidence: 52%
“…Previously reported that enhanced LPS‐induced inflammation was via stiffness‐dependent stimulation and LPS could stimulate changes in cellular mechanical properties in terms of elasticity and viscoelasticity. 27 , 28 It has been shown that LPS could directly induce cell swelling response in a TLR4‐dependent manner. 29 Of note, TRPV4 regulates LPS‐stimulated macrophage phagocytosis in a matrix stiffness‐dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IBD-associated mucosal inflammation is associated with aberrant DNA methylation whereas SCFAs exhibit anti-inflammatory effects in IBD via IECs-induced changes in the transcription of inflammatory markers ( 216 218 ). On the other hand, gut dysbiosis, the presence of bacterial pathogens or LPS affect epigenetic mechanisms connected to inflammation and metabolism by acting on host DNMTs or by producing the enzyme itself ( 219 222 ).…”
Section: Scfa-epigenetic Regulationmentioning
confidence: 99%